Concern Over Internal, External, and Incidence Validity in Studies of Child‐Care Quantity and Externalizing Behavior Problems. (30th January 2017) - Dearing, Eric; Zachrisson, Henrik D.
Abstract: Literature reviews have concluded that extensive time in early child care is associated with frequent externalizing behavior problems in children. In this article, we address three domains of validity in the work underlying these conclusions: internal, external, and incidence validity. Regarding internal validity, most studies rely on covariate‐adjusted correlations, an approach that is especially vulnerable to selection bias. In studies using more rigorous approaches to reduce selection bias, results are mixed and often inconsistent with the hypothesis that a high quantity of child care causes externalizing problems. Regarding external validity, the field has relied too heavily on U.S. samples. We call for more international replications to allow for sociopolitical variations. Regarding incidence validity, study designs have the widest relevance when structured to address the opportunities and constraints families face today. We suggest researchers ask questions about child‐care quantity that maximize validity in these three domains.